Expressions of growth differentiation factor-9 (gdf-9) of bovine cumulus-oocyte complex in peritoneal fluid culture of infertile patients with endometriosis - Mira Myrnawati (Departemen Obstetri dan Ginekologi Fakultas Kedokteran Universitas Airlangga, 2013)
The decrease of GDF-9 production may impair oocyte granulosa cell communication and lead to failure of fertilization and embryonic development. The objective of this study was to study expression of growth differentiation factor-9 (GDF-9) cumulus-oocyte complex in peritoneal culture of infertile patients with endometriosis. Peritoneal fluid were collected from infertile patients undergoing diagnostic laparoscopy and classified into non-endometriosis, mild endometriosis, and severe endometriosis according to laparoscopic finding. Cumulus-oocyte complex (COC) were aspirated from antral follicle derived from bovine ovary from local abattoirs. COC were then placed in tissue culture medium-199 (TCM-199) and divided into four group of cultere. First group contain TCM-199 as a medium served as control group, while second, third, and four groups medium were added accordingly with 3% of peritoneal fluid of non endometriosis, mild endometriosis, and severe endometriosis. These four groups were incubated in 5% CO2 at 38oC for 20 hours and COC were eventually fixated in object glasses, stained by immunocytochemistry, and followed by measurement of GDF-9 expression. Statistic analysis using Kruskal Wallis test showed differences of GDF-9 expression in four culture groups. Mann-Whitney test revealed that GDF-9 expression in endometriosis group (mild and severe) were significantly lower compared with control and non-endometriosis group and expression in severe endometriosis group were significantly lower than in mild endometriosis one (p < 0.05). In conclusion,GDF-9 expressions of bovine COC cultured in peritoneal fluid of infertile patients with endometriosis were lowered compared with that of control and non-endometriosis group and this decrease was in proportion with severity of endometriosis.(MOG 2013;21:71-76)